2008
DOI: 10.1002/chem.200800553
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Linear Free‐Energy Relationships Combined with Activation Parameters Assigns a Concerted Mechanism to Alkaline Hydrolysis of X‐Substituted Phenyl Diphenylphosphinates

Abstract: A kinetic study is reported for alkaline hydrolysis of X-substituted phenyl diphenylphosphinates (1 a-i). The Brønsted-type plot for the reactions of 1 a-i is linear over 4.5 pK(a) units with beta(lg)=-0.49, a typical beta(lg) value for reactions which proceed through a concerted mechanism. The Hammett plots correlated with sigma(o) and sigma(-) constants are linear but exhibit many scattered points, while the corresponding Yukawa-Tsuno plot results in excellent linear correlation with rho=1.42 and r=0.35. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…The data in parentheses for the reactions of the P=O centered substrates 1a , 1b , and 1i were taken from Um et al…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The data in parentheses for the reactions of the P=O centered substrates 1a , 1b , and 1i were taken from Um et al…”
Section: Resultssupporting
confidence: 89%
“…The Brønsted‐type plots for the reactions of 1a to 1i and 2a to 2i are linear with β lg = −0.49 ± 0.04 ( R 2 = 0.980) and −0.43 ± 0.04 ( R 2 = 0.975), respectively. A linear Brønsted plot with β lg = −0.5 ± 0.1 is typical for reactions reported to proceed via a concerted mechanism . We have reported that the reactions of 1a to 1i proceed through a concerted mechanism, partly on the basis of such linear Brønsted‐type plots with β lg = −0.49 .…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] As shown in Scheme 1, aminolysis of esters is generally known to proceed through a stepwise pathway with a zwitterionic tetrahedral intermediate T ± , in which the rate-determining step (RDS) is dependent on the basicity of the incoming amine and the leaving group, or through a concerted mechanism depending on the reaction conditions (e.g., the nature of electrophilic center and reaction medium).…”
Section: Introductionmentioning
confidence: 99%